Bliese System: A Web-Based Management System For Small Business - Shahrul Amer, Nur Diyana; A. Mostafa, Salama (Applied Information Technology And Computer Science, 2022)
Most people start to get involved in the business world and manage their business manually which causes duplicated records, not tally stocks, and loss of manual records. This will also cause inconvenience for the business owner who does not own a management system. Thus, this project aims to develop a management system for small business which objectives are to design a management system, develop, implement, and perform alpha and beta testing for the developed The Bliese System. After a little research was done, the inventory system, web-based technology, and prototyping methodology are suitable to be implemented along with the development of this project. The implementation using PHP and MySQL has been done, and testing results show that the system is developed according to the objectives. The results from alpha and beta testing shows that the system is developed as expected and accepted by the owner and end-users. This system helps the owner of the company and users have a better system in keeping stocks and records updated and ease the process of purchasing and management. Although there are limitations figured out, improvisation can be done in future work such as including promotions in the main page to let the user know about current promotions, upgrading the cart to allow user to select which product in cart to be checked out, include more information about the owner’s store in About Us page and include other payment methods such as Online Transfer, TouchnGo e-Wallet or payment a7-Eleven store. These improvements towards the system will eventually make the system more attractive, more flexible for other devices, and more user-friendly.